2015
DOI: 10.1016/j.poly.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Engineering 2D→2D parallel interpenetration using long alkoxy-chain substituents

Abstract: The structural consequences of reducing the length of the alkoxy substituents on going from the ditopic ligand 1,4-bis(n-octoxy)-2,5-bis(4,2':6',4''-terpyridin-4'-yl)benzene (1) to 1,4-bis(methoxy)-2,5-bis(4,2':6',4''-terpyridin-4'-yl)benzene (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…We have demonstrated that the length of such tails can have a significant impact on the outcome of assembly processes [13,14,15]. Single crystals grown by layering a MeOH solution of Co(NCS) 2 over a CHCl 3 solution of 8 were not of X-ray quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that the length of such tails can have a significant impact on the outcome of assembly processes [13,14,15]. Single crystals grown by layering a MeOH solution of Co(NCS) 2 over a CHCl 3 solution of 8 were not of X-ray quality.…”
Section: Resultsmentioning
confidence: 99%
“…Rotation about the C–spacer bonds permits the node to have limiting planar or approximately tetrahedral geometries, and the directionality of the assembly can be modified by switching from 4,2’:6’,4”-tpy to 3,2’:6’,3”-tpy domains. We have recently employed such ditopic ligands in which the spacer (Scheme 1c) is a 1,4-C 6 H 4 ring to assemble parallel interpenetrating 2D→2D sheets [13,14,15] and 3D-metal-organic frameworks (MOFs) [15,16]. Going to a ferrocen-1,1’-yl spacer introduces rotational freedom and, in [{Zn 2 ( 1 )Cl 4 }∙3CHCl 3 ] n where 1 = 1,1’-bis(4,2’:6’,4”-terpyridin-4’-yl)ferrocene (Scheme 2), the ligand adopts a cisoid-conformation, leading to a double-stranded 1D-polymer chain [17].…”
Section: Introductionmentioning
confidence: 99%
“…going from n octoxy to methoxy functionalization) causes the profile of the corrugated sheet to change. 14 (5) . 2MeOH] n , the alkoxy chain lies over two pyridine rings of a 4,2':6',4''-tpy unit (Fig.…”
Section: Alkoxy Chains: 2d→ → → →2d Parallel Interpenetrated Sheetsmentioning
confidence: 99%
“…In contrast, combining 2 (Scheme 3) with ZnCl 2 or ZnBr 2 leads to 2D-sheets in which the ligands are the unique nodes. 13,14 While the (4,4) (2)}] n , and are threaded within the interpenetrated sheets. We have previously suggested that the long chains may assist in directing the assembly process.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of micelles, which aggregate to form cylindrical vesicles, is an alternate possibility (16). Constable, Housecroft et al (38)(39)(40)(41) recently studied the effects of alkylation (C 8 vs. Me) on gauge the effect of counterions and solvent on morphology with this system, 4 (Cl − ) was cast utilising a solvent mixture of MeCN/CHCl 3 (5/1). Disordered lamellae but no rods were observed (S10); however, the TEMs of 4 (Cl − ) cast from CHCl 3 /MeoH (2:1) are shown in Figures 9 and 10.…”
Section: Microscopymentioning
confidence: 99%